2020
DOI: 10.1038/s41392-020-00261-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: key players in cancer and potential therapeutic strategy

Abstract: Exosomes are extracellular vesicles secreted by most eukaryotic cells and participate in intercellular communication. The components of exosomes, including proteins, DNA, mRNA, microRNA, long noncoding RNA, circular RNA, etc., which play a crucial role in regulating tumor growth, metastasis, and angiogenesis in the process of cancer development, and can be used as a prognostic marker and/or grading basis for tumor patients. Hereby, we mainly summarized as followed: the role of exosome contents in cancer, focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
561
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 791 publications
(566 citation statements)
references
References 163 publications
4
561
0
1
Order By: Relevance
“…Collectively, exosomes can cause tumor cells to acquire resistance by various pathways, including the reduction of intracellular drug concentrations, induction of EMT, activation of anti-apoptotic pathways, alteration of critical survival signal transduction pathways, and modulation of the immune system ( Mashouri et al, 2019 ; Steinbichler et al, 2019 ; Dai et al, 2020 ).…”
Section: Tme-driven Adaptive Mechanisms Of Therapy Resistancementioning
confidence: 99%
“…Collectively, exosomes can cause tumor cells to acquire resistance by various pathways, including the reduction of intracellular drug concentrations, induction of EMT, activation of anti-apoptotic pathways, alteration of critical survival signal transduction pathways, and modulation of the immune system ( Mashouri et al, 2019 ; Steinbichler et al, 2019 ; Dai et al, 2020 ).…”
Section: Tme-driven Adaptive Mechanisms Of Therapy Resistancementioning
confidence: 99%
“…These are microvesicles (also referred to as ectosomes) of 100–1000 nm that are formed by plasma membrane shedding, and exosomes of 30–150 nm that derive from the endocytic pathway and are released when multivesicular bodies (MVBs) fuse with the plasma membrane [ 92 , 93 ]. Exosomes, in particular, have gained substantial attention over the last few years as experimental evidence has demonstrated that they contribute to the development and progression of human diseases, including cancer [ 92 , 94 , 95 ]. It has been demonstrated that cancer cells release more exosomes compared to normal cells as a response to pathophysiological conditions like hypoxia and low pH in the tumor microenvironment or to oncogenic activities within the cells [ 96 , 97 , 98 ].…”
Section: Liquid Biopsies On Breast Cancermentioning
confidence: 99%
“…Importantly, exosomes are also detected in body fluids, including blood, suggesting that they can act as mediators of long-distance cellular signaling [ 99 , 100 , 101 ]. In cancer, exosomes may promote tumor cell migration, invasion, and formation of distant metastatic niches [ 92 , 94 , 98 ]. They have also been shown to play a role in cancer cell immune evasion [ 102 ].…”
Section: Liquid Biopsies On Breast Cancermentioning
confidence: 99%
“…Likewise, exosomal miR-106b-3p is abundantly detected in the serum of metastatic colorectal cancer patients, induces tumor cell migration, invasion and epithelial-to-mesenchymal transition (EMT), and correlates with poor survival [ 69 , 70 ]. Other pro-invasive factors transported via tumor-released EVs include TGF-β, caveolin-1, HIF1α and β-catenin, all of which were shown to promote EMT, extracellular matrix remodeling and metastatic niche formation [ 71 ]. Examples come from multiple cancer types: colorectal cancer, where EVs transfer mutated β-catenin to modulate Wnt signaling and enhance tumor growth [ 72 ]; gastric cancer, where EV-mediated TGF-β transfer and subsequent activation of the TGF-β/Smad pathway assists in the formation of metastatic niches [ 73 ]; and nasopharyngeal carcinoma, where EVs with enhanced levels of HIF1α increase the migration and invasion of tumor cells [ 74 ].…”
Section: Extracellular Vesicles—function In Cancermentioning
confidence: 99%